Distribution and development patterns in Antarctic asteroids - Pérez, Analía Fernanda (2024)
Introduction: Echinoderms are dominant in terms of abundance and diversity; particularly asteroids play an important role in Antarctic benthic communities. Objective: The aim of the present work was to review the bathymetric distribution, specific composition, occurrence and species richness of asteroid species inhabiting South Orkney, South Shetland and Palmer Archipelago, located in the Antarctic Peninsula. Aspects of the developmental patterns of the species found are also included. Methods: We used data acquired during the 2012 and 2013 Antarctic Summer Campaigns aboard the Oceanographic Vessel “Puerto Deseado”. Sampling stations were located in three archipelagos located in the Antarctic Peninsula: South Orkney (SO), South Shetland (SS) and Palmer Archipelago (PA). A total of 28 fishing hauls were made and 436 individuals were photographed and processed. The maximum radius (mm) of each individual, the macroscopic characteristics of the gonads and the presence of embryos were registered. A review of the taxonomic status, bathymetric and geographical distribution area of the sampled species was carried out based on bibliographic records and databases. A hierarchical grouping was used to analyze species composition among the different areas. Results: Asteroids were obtained in all sampling stations (occurrence: 100 %) between 52.7 and 987 m depth. 21 species were recorded, the bathymetric distribution was not broadened in any of them, and the geographical distribution area of six species was expanded. Species richness was equal in SS and PA and higher than in SO, coinciding with the presence of two regional groups with a similar faunal composition. Seventy-two percent of the recorded species present pelagic development (planktotrophic larvae = 17 %, and lecithotrophic larvae = 55 %) and 28 % non-pelagic development (retained larvae = 17 %, and direct development = 11 %). Conclusions: In the three archipelagos, the majority development pattern was pelagic with lecithotrophic nutrition. All the species found in this study are shared with the sub-Antarctic region, highlighting the importance of the Malvinas Current in the dispersal of species from Antarctica.